Human Rights in Indonesia: Between Protection, Fulfillment, and Law Enforcement - Khoiril Huda; Ridwan Arifin (Universitas Negeri Semarang, 2018)
The realm of human rights presents a complex interplay between protection, fulfillment, and law enforcement, particularly evident in the case of Indonesia. This abstract delves into the multifaceted landscape of human rights within the Indonesian context. Indonesia's transition to democracy marked a important juncture for human rights. The government ratified numerous international treaties and established a National Human Rights Commission, reflecting its commitment to protection. However, challenges persist as minority rights, notably those of religious and ethnic groups, face intermittent infringement, revealing gaps between rhetoric and reality. Fulfillment of rights poses another intricate facet. Economic and social rights, essential for human dignity, demand equitable distribution of resources. Indonesia's progress is discernible in poverty reduction and improved healthcare and education. Nevertheless, regional disparities and the indigenous population's marginalization warrant attention to ensure holistic rights fulfillment. Effective law enforcement remains central to the human rights discourse. The nation's counterterrorism efforts have sometimes raised concerns regarding due process and freedom of expression. Additionally, the protection of civil liberties necessitates consistent law enforcement reforms, emphasizing accountability, transparency, and the independence of the judiciary.